Arteriovenous differences across human adipose and forearm tissues after overnight fast. - Coppack, S; Frayn, K; Humphreys, S; Whyte, P; Hockaday, T (1990)
Measurements of arteriovenous differences across subcutaneous abdominal tissue (mainly adipose) and deep forearm tissue (mainly muscle) were made on 25 occasions in normal subjects after an overnight fast. Adipose tissue was shown to be strongly lipolytic (releasing nonesterified fatty acids and glycerol), to clear circulating triacylglycerol, glucose, ketone bodies and acetate, and to produce lactate. Uptake of circulating carbohydrate and ketones was sufficient to account for only 51% of the adipose tissue oxygen consumption, implying that adipose tissue utilizes fuel(s) stored within it. The mean fractional re-esterification rate of fatty acids in adipose tissue was 13% to 19%. Arteriovenous differences were converted to fluxes of carbon atoms to compare the movements of different fuels. (Amino acids were not included in these calculations.) Adipose tissue after an overnight fast was a net exporter of carbon, whereas in resting muscle the uptake of carbon atoms from circulating carbohydrate and lipid fuels approximately balanced the CO2 production. Fatty acids were the main form in which carbon left adipose tissue, and the main source of carbon atoms entering the resting forearm.